Analisis Pengaruh Dimensi Expressing Positif Feelings Terhadap Keputusan berkunjung ke Puncak Mas Lampung - Alditia Detmuliati; Dira Salsabilla; Heri Setiawan (Politeknik Negeri Sriwijaya, 2021)
This research aims to determine the significance of Electronic Word of Mouth both partially and simultaneously on tourists decision to visit at Puncak Mas Lampung. The research methods used descriptive method with quantitative approach. Total population drawn from the data one years back as many as 210.000 people. The sample technique used is convenience sampling as many as 100 respondent. Techniques of collecting data through questionnaires, documentation and literature studies. Analysis data was procesed by using the SPSS program version 24 with analysis tecnique used is multiple regression. The result of this research show that partially concern for other has not positive and significant impact on tourists decision to visit. But expressing positive feelings, helping the company and platform assiatance has positive and significant impact on tourists decision to visit. Concern for other, expressing positive feelings, helping the company and platform assistance simultaneously have positive and significant impact on tourists decision to visit.